Thoughts on the Worry and Terror that Nursing Students Experience During Clinical Practicums - Mohammed Ali Al Brahim; Fatemah Abdullah Ashwan; Ali Bunaqah; Radia Abdullah Al Ashoor; Basmah Abdulaziz Alateeq; Reham Mohammed Alhamad; Zainab Ali H Alessa; Abdullah Amer Ali Alasiri; Ali Drwish Alasiri; Mohammed Fayi Muhyialdeen Mukhalid; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Anxiety and fear are prevalent emotional responses among nursing students, particularly during clinical practicums, and can significantly impact their academic performance and professional development. This paper examines the sources of these emotional states, focusing on the perceptions of nursing students regarding preceptor behavior and the role of relational teaching-learning processes in shaping their professional identity. Anxiety is often triggered by concerns about making mistakes, failing, or lacking knowledge, while fear typically arises during specific tasks or assessments. The support and attitudes of preceptors play a pivotal role in alleviating or exacerbating these emotions, and a lack of proper guidance can negatively affect students’ learning experiences. Relational processes, including trust, moral courage, and sensitivity, are essential for fostering positive relationships between students and preceptors, contributing to both personal and academic growth. Furthermore, the development of leadership skills and teamwork is crucial for nursing students, as these qualities are integral to their future roles in healthcare. Intrinsic and extrinsic factors, such as self-demanding behavior and social comparison, also influence students’ self-confidence and motivation. The study underscores the importance of addressing these emotional challenges early in the nursing education process to improve student outcomes and prepare them to become competent and compassionate healthcare professionals. The paper calls for strategic investments in nursing education and a supportive environment to foster the development of the next generation of nurses, in line with global healthcare needs.